Influence of mental health conditions and symptoms on contraceptive use among adolescent girls and young women: a scoping review - Luthuli, Muziwandile Qiniso; Nkala-Dlamini, Busisiwe; Nzuza-Moroe, Nomfundo (Frontiers in Reproductive Health, 2025)
BackgroundAdolescent girls and young women (AGYW) across the globe face a high risk of mental health challenges and unintended pregnancies, which are often complex and intertwined within their psychosocial environments. While earlier studies have examined contraceptive use, the influence of mental health conditions and symptoms on a broader range of contraceptive options among AGYW has not been thoroughly investigated.ObjectivesThis scoping review aims to map and synthesize peer-reviewed literature to understand how mental health conditions and symptoms influence contraceptive use among AGYW globally.MethodsThis review followed Arksey and O'Malley's framework. Databases searched included PubMed, MEDLINE, PsycINFO, CINAHL, Psychology and Behavioral Sciences Collection, Web of Science, and African Journals Online. We included studies on AGYW aged 10–25 years that addressed how mental health conditions and symptoms influence contraceptive use.ResultsOf the 9,817 records identified, only 17 studies met inclusion criteria. Depression (65%; n = 11) was the most frequently studied mental health factor, followed by stress (29%; n = 5), proxies for mental distress (24%; n = 4, including antidepressants and psychotropic drug use), and anxiety (18%; n = 3). Hormonal contraceptives (HCs) (100%; n = 17) were the most studied methods. Among the included studies, 71% (n = 12) found that mental health conditions and symptoms, such as depression, anxiety, psychological distress, stress, antidepressants, and psychotropic drug use, were associated with lower odds of HC use. Conversely, 29% (n = 5) found these factors to be associated with higher odds of HC use, particularly oral and non-oral methods. Stress and depression were associated with lower odds of consistent contraceptive use, while anxiety demonstrated mixed effects. Two studies reported no association between mental health factors and contraceptive use. Eleven studies focused on adolescents and six on young adults, showing a bidirectional influence between mental health and contraceptive use, with inconsistent findings across age groups.ConclusionsMental health factors affect contraceptive use in different ways. Depression and stress reduce the odds of consistent HC use, especially among non–oral contraceptive users, while anxiety shows mixed outcomes. Findings underscore the complex influence of mental health factors on contraceptive behavior among AGYW and highlight the need for age–specific policies and interventions tailored to this high–priority population.